Students’ Collaboration Skills Profile in Case Method Learning: A Cognitive-Behavioristic Perspective - Muhammad Aqmal Nurcahyo; Sujarwo Sujarwo; Bambang Saptono; Yunika Afryaningsih; Dessy Setyowati; Risdiana Andika Fatmawati (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: The increasing demand for 21st century competencies highlights the importance of collaboration skills in higher education. However, limited studies have examined how integrated cognitive-behavioristic grouping strategies shape specific dimensions of students’ collaboration skills. This study aims to analyze the profile of students’ collaboration skills within a cognitive-behavioristic grouping framework implemented through case-method-based collaborative learning. This research employed a qualitative descriptive approach embedded in a lesson study design involving 30 third-semester students of the Elementary School Teacher Education Program. Data were collected through structured observation sheets, field notes, student worksheets, voice recordings, and documentation to ensure triangulation. Although descriptive statistics were used to calculate percentage distributions, the analysis remained qualitative-descriptive, focusing on interpreting observable collaborative behaviors across five aspects: contribution, time management, problem solving, working with others, and investigation techniques. The findings indicate that the overall collaboration skill level reached 72,83% (collaborative category), with stronger performance in interpersonal aspects than in higher-order investigative competencies. These results suggest that cognitive-behavioristic grouping effectively reinforces cooperative behaviors but requires additional cognitive scaffolding to optimize analytical and inquiry skills. The novelty of this study lies in integrating cognitive and behavioristic dimensions as a structured basis for heterogeneous grouping and in examining collaboration skills across specific measurable aspects. The study contributes theoretically to collaborative learning design by bridging behavioral engagement and cognitive depth, and practically by offering a structured grouping model that supports balanced collaborative development in higher education.Abstrak: Tuntutan kompetensi abad ke-21 menegaskan pentingnya keterampilan kolaborasi dalam pendidikan tinggi. Namun, penelitian yang mengkaji bagaimana strategi pengelompokan berbasis kognitif-behavioristik memengaruhi dimensi spesifik keterampilan kolaborasi masih terbatas. Penelitian ini bertujuan untuk menganalisis profil keterampilan kolaborasi mahasiswa dalam kerangka pengelompokan kognitif-behavioristik yang diimplementasikan melalui pembelajaran kolaboratif berbasis case method. Penelitian ini menggunakan pendekatan kualitatif deskriptif yang terintegrasi dalam desain lesson study dengan melibatkan 30 mahasiswa semester III Program Studi Pendidikan Guru Sekolah Dasar. Data dikumpulkan melalui lembar observasi terstruktur, catatan lapangan, lembar kerja mahasiswa, rekaman suara, dan dokumentasi untuk menjamin triangulasi data. Meskipun statistik deskriptif digunakan untuk menghitung persentase, analisis tetap berorientasi kualitatif dengan fokus pada interpretasi perilaku kolaboratif yang teramati pada lima aspek, yaitu kontribusi, manajemen waktu, pemecahan masalah, bekerja sama, dan teknik investigasi. Hasil penelitian menunjukkan bahwa tingkat keterampilan kolaborasi secara keseluruhan mencapai 72,83% (kategori kolaboratif), dengan kekuatan pada aspek interpersonal dibandingkan aspek investigatif tingkat tinggi. Temuan ini menunjukkan bahwa pengelompokan kognitif-behavioristik efektif memperkuat perilaku kooperatif, namun masih memerlukan scaffolding kognitif untuk mengoptimalkan kemampuan analitis dan inkuiri. Kebaruan penelitian ini terletak pada integrasi dimensi kognitif dan behavioristik sebagai dasar pengelompokan heterogen serta pengukuran keterampilan kolaborasi secara spesifik. Penelitian ini berkontribusi secara teoretis dalam menjembatani dimensi perilaku dan kognitif dalam desain pembelajaran kolaboratif, serta secara praktis menawarkan model pengelompokan yang mendukung pengembangan kolaborasi yang lebih seimbang di pendidikan tinggi.